Neonatal vascularization and oxygen tension regulate appropriate perinatal renal medulla/papilla maturation. Issue 5 (April 2016) - Phua, Yu Leng; Gilbert, Thierry; Combes, Alexander; Wilkinson, Lorine; Little, Melissa H
Abstract: Congenital medullary dysplasia with obstructive nephropathy is a common congenital disorder observed in paediatric patients and represents the foremost cause of renal failure. However, the molecular processes regulating normal papillary outgrowth during the postnatal period are unclear. In this study, transcriptional profiling of the renal medulla across postnatal development revealed enrichment of non‐canonical Wnt signalling, vascular development, and planar cell polarity genes, all of which may contribute to perinatal medulla/papilla maturation. These pathways were investigated in a model of papillary hypoplasia with functional obstruction, the Crim1 KST264 / KST264 transgenic mouse. Postnatal elongation of the renal papilla via convergent extension was unaffected in the Crim1 KST264 / KST264 hypoplastic renal papilla. In contrast, these mice displayed a disorganized papillary vascular network, tissue hypoxia, and elevated Vegfa expression. In addition, we demonstrate the involvement of accompanying systemic hypoxia arising from placental insufficiency, in appropriate papillary maturation. In conclusion, this study highlights the requirement for normal vascular development in collecting duct patterning, development of appropriate nephron architecture, and perinatal papillary maturation, such that disturbances contribute to obstructive nephropathy. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.